The relationship mammalian p38 with human health and its homolog Hog1 in response to environmental stresses in Saccharomyces cerevisiae - Du, Gang; Zheng, Kaifang; Sun, Cunying; Sun, Mingyue; Pan, Jie; Meng, Dan; Guan, Wenqiang; Zhao, Hui (Frontiers in Cell and Developmental Biology, 2025)
The mammalian p38 MAPK pathway plays a vital role in transducing extracellular environmental stresses into numerous intracellular biological processes. The p38 MAPK have been linked to a variety of cellular processes including inflammation, cell cycle, apoptosis, development and tumorigenesis in specific cell types. The p38 MAPK pathway has been implicated in the development of many human diseases and become a target for treatment of cancer. Although MAPK p38 pathway has been extensively studied, many questions still await clarification. More comprehensive understanding of the MAPK p38 pathway will provide new possibilities for the treatment of human diseases. Hog1 in S. cerevisiae is the conserved homolog of p38 in mammalian cells and the HOG MAPK signaling pathway in S. cerevisiae has been extensively studied. The deep understanding of HOG MAPK signaling pathway will help provide clues for clarifying the p38 signaling pathway, thereby furthering our understanding of the relationship between p38 and disease. In this review, we elaborate the functions of p38 and the relationship between p38 and human disease. while also analyzing how Hog1 regulates cellular processes in response to environmental stresses. 1, p38 in response to various stresses in mammalian cells.2, The functions of mammalian p38 in human health.3, Hog1 as conserved homolog of p38 in response to environmental stresses in Saccharomyces cerevisiae. 1, p38 in response to various stresses in mammalian cells. 2, The functions of mammalian p38 in human health. 3, Hog1 as conserved homolog of p38 in response to environmental stresses in S. cerevisiae.